Transcranial Magnetic Stimulation in Neuropsychiatry 2018
DOI: 10.5772/intechopen.72787
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Treating Impulsivity in Borderline Personality Disorder and Attention Deficit/Hyperactivity Disorder

Abstract: The need for novel treatment approaches that target impulsivity symptoms in neuropsychiatric disorders is clear. Repetitive transcranial magnetic stimulation (rTMS) allows selective neuromodulation of regions involved in the functional neuroanatomy of neuropsychiatric disorders. This chapter presents impulsivity in psychiatry, especially in borderline personality disorder (BPD) and attention-deficit hyperactivity disorder (ADHD), its neural underpinnings, and its possible treatment by rTMS. We reviewed availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 106 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…The median population prevalence is estimated to be 1.6% but could be as high as 5.9% 1 . BPD is characterised by a pervasive pattern of deficits in emotional regulation, impulsivity, behavioural control and self‐identity 2,3 . Self‐injurious behaviour and suicidality associated with BPD are challenging to manage.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The median population prevalence is estimated to be 1.6% but could be as high as 5.9% 1 . BPD is characterised by a pervasive pattern of deficits in emotional regulation, impulsivity, behavioural control and self‐identity 2,3 . Self‐injurious behaviour and suicidality associated with BPD are challenging to manage.…”
mentioning
confidence: 99%
“…Functional neuroimaging and neuropsychology studies have identified a dysfunctional frontolimbic network that may be involved in clinical symptoms, including emotional instability and impulsivity 2,3 . Positron emission tomography (PET) imaging has been shown to have an altered metabolism in the prefrontal region of patients 2,3 .…”
mentioning
confidence: 99%
See 2 more Smart Citations